Hot-Air Flow Rolling Dry-Blanching Pretreatment Improves the Drying Quality of Acanthopanax sessiliflorus by Increasing the Drying Rate and Inactivating Enzymes - Nan-nan An; Shi-yu Zhao; Dong Li; Yong Wang; Li-jun Wang (Foods, 2022)
The processing of Acanthopanax sessiliflorus has attracted interest due to its health benefits. In this work, an emerging blanching technology, called hot-air flow rolling dry-blanching (HMRDB), was employed to treat A. sessiliflorus before drying. The effects of varied blanching times (2–8 min) on enzyme inactivation, drying characteristics, bioactive compound retention, and microstructure were examined. The results demonstrated that blanching for 8 min rendered polyphenol oxidase and peroxidase nearly inactive. The blanching process reduced the drying time of samples by up to 57.89% compared to an unblanched sample. The Logarithmic model showed good fitting performance for the drying curves. The total phenolic and flavonoid content of the dried product increased as blanching time increased. The total anthocyanin content of the samples blanched for 6 min was 3.9 times higher than that of the unblanched samples, and 8 min of blanching produced the greatest DPPH• and ABTS• scavenging capabilities. The retention of active compounds in a dried product is a result of the inactivation of enzymes and a reduced drying period. Changes in the porous structure of the blanched samples would be responsible for the accelerated drying rate, according to microstructural analysis. These results indicate that HMRDB enhances the drying process and improves drying quality when applied to A. sessiliflorus before drying.